Territori i identitat en la narrativa de Carme Riera - Carme Gregori Soldevila (Catalonia)
This paper analyses the relations between thematization of the territory and symbolic elaboration of identity in Carme Riera’s narrative: in two inicial short story collections, Te deix, amor, la mar com a penyora and Jo pos per testimoni les gavines, and in two novels: Dins el darrer blau and La meitat de l’ànima. The aim of the research is to show that, according to the works, the identity value of Mallorca arises either from a sentimental perspective, or in terms of moral or in terms of cultural transmission, in literary key.